Ships time in port. (2018) - Slack, Brian; Comtois, Claude; Wiegmans, Bart; Witte, Patrick
Much of the success of containerisation is due to time economies, particularly the reduction in the duration of port calls. Although vessels now spend a small amount of time in port compared with the time at sea, it is still a cost factor. The focus of this study is the amount of time container vessels spend in port. The average vessel turnaround times (ATTs) involving 70 ports of call involved in four major trade routes are examined. The principal research questions addressed are: how do ATTs vary among ports and how is this time metric related to port performance? ATTs are compared with traffic volumes measures of port efficiency. The results are weak and lead to a hypothesis that ATTs are differentiated regionally and functionally, rather than globally. Evidence is presented for this hypothesis. Several theoretical issues are considered arising from the results and questions for further research are presented.